Hot molecular core candidates in the Galactic center 50 km s−1 molecular cloud. (22nd June 2021) - Miyawaki, Ryosuke; Tsuboi, Masato; Uehara, Kenta; Miyazaki, Atsushi
Abstract: We present results based on 2^′ ′_.5 -resolution observations using the Atacama Large Millimeter/Submillmeter Array (ALMA) of the Galactic center molecular cloud G−0.02−0.07, or the 50 km s −1 molecular cloud (50 MC), in the SO ( NJ = 22 –11 ) line and 86 GHz continuum emission, the combination of which is considered to trace "hot molecular core candidates" (HMCCs) appearing in the early stage of massive-star formation. In the 86 GHz continuum image, we identified nine dust cores in the central part of the 50 MC, in which four famous compact H ii regions are located. No new ultra-compact H ii regions were found. We also identified 28 HMCCs in the 50 MC with the SO line. The overall SO distribution had no clear positional correlation with the identified H ii regions. The HMCCs in the 50 MC showed a variety of association and non-association with dust and Class I CH3 OH maser emissions. The variety suggests that they are not in a single evolutionary stage or environment. Nevertheless, the masses of the identified HMCCs were found to be well approximated by a single power law of their radii, M LTE /( M⊙ ) = 5.44 × 10 5 [ r /(pc)] 2.17 at T ex = 50–100 K. The derived HMCC masses were larger than those of the molecular cores with the same radii in the 50 MC, and also than those of the molecular clumps in the Galactic disk. Additional observations are needed to confirm the nature of these HMCCs in the 50 MC.